Clinical Application of Adaptive Immune Therapy in MSS Colorectal Cancer Patients - Wang, Danyang; Zhang, Hangyu; Xiang, Tao; Wang, Gang (Frontiers in Immunology, 2021)
Colorectal cancer (CRC) is one of the most common cancer around the world. However, treatment outcome of immunotherapy in MSS CRC remains unsatisfied according to the current situation. As the majority CRC display a molecular MSS/pMMR profile, it is particularly meaningful to explore clinical applications of adaptive immune therapy to MSS CRC patients. In this review, we summarized the therapeutic approaches of adoptive immune therapy in the treatment of MSS CRCs, including cytokines, therapeutic cancer vaccines, adoptive T-cell therapy and immune checkpoint inhibitors.